Assessment of wheat variety adoption in Bangladesh through DNA fingerprinting. Issue 5 (2nd August 2021) - Gade, Poornima; Alam, M Ashraful; Barma, Naresh C.D.; Majumder, Rituparna; Garapaty, Rijuta; Paranjape, Vijay Dattatraya; Killian, Andrzej; Vijayaraghavan, K.; Kabir, Md. Rezaul; Hakim, Md. Abdul; Islam, Md. Zaherul; Hossain, Md. Mahamudul; et al.
Abstract: Wheat ( Triticum aestivum L.) demand in Bangladesh has increased significantly in recent years, becoming the second major staple cereal after rice ( Oryza sativa L.). Domestic production of wheat accounts for only 16% of domestic use. More than 30 wheat varieties have been released in the past 30 yr by the Bangladesh Wheat and Maize Research Institute (BWMRI). In the last 10 yr alone, nine varieties with improved yield and disease resistance have been released. Bangladesh and the BWMRI lack the regulatory framework and infrastructure to accurately track the rate of adoption of these new releases. To determine the adoption of these varieties across the country, DNA fingerprinting of wheat samples was conducted across the six wheat growing regions in Bangladesh during the 2018–2019 cropping season. A reference library was established to compare and identify the wheat samples collected from farmers' fields. Wheat grain samples collected from the fields and breeders' lines were genotyped using Diversity Arrays Technology sequencing (DArTseq)‐based single nucleotide polymorphism (SNP) markers. Of the 1, 791 samples collected from farmers' fields, 68% were identified as varieties released after 2000 and 32% matched with older varieties. Among the varieties grown, BARI Gom 25 represented 29% of the collected samples followed by 23% of BARI Gom 24 and 16% of BARI Gom 26. These three most common varieties were well distributed across the six regions and have broad adoption. Core Ideas: High throughput DNA fingerprinting can be efficiently used for assessment of varietal adoption. 68% of samples identified as varieties released after 2000 and 32% matched with older varieties. Improving management of wheat breeder seed is essential for accurate adoption studies.